Hydrogeological responses to incoming materials at the erosional subduction margin, offshore Osa Peninsula, Costa Rica. (21st August 2015) - Kameda, Jun; Harris, Robert N.; Shimizu, Mayuko; Ujiie, Kohtaro; Tsutsumi, Akito; Ikehara, Minoru; Uno, Masaoki; Yamaguchi, Asuka; Hamada, Yohei; Namiki, Yuka; Kimura, Gaku
Abstract: Bulk mineral assemblages of sediments and igneous basement rocks on the incoming Cocos Plate at the Costa Rica subduction zone are examined by X‐ray diffraction analyses on core samples. These samples are from Integrated Ocean Drilling Program Expedition 334 reference Site U1381, ∼ 5 km seaward of the trench. Drilling recovered approximately 100 m of sediment and 70 m of igneous oceanic basement. The sediment includes two lithologic units: hemipelagic clayey mud and siliceous to calcareous pelagic ooze. The hemipelagic unit is composed of clay minerals (∼50 wt.%), quartz (∼5 wt.%), plagioclase (∼5 wt.%), calcite (∼15 wt.%) and ∼30 wt.% of amorphous materials, while the pelagic unit is mostly made up of biogenic amorphous silica (∼50 wt.%) and calcite (∼50 wt.%). The igneous basement rock consists of plagioclase (∼50–60 wt.%), clinopyroxene (∼>25 wt.%), and saponite (∼15–40 wt.%). Saponite is more abundant in pillow basalt than in the massive section, reflecting the variable intensity of alteration. We estimate the total water influx of the sedimentary package is 6.9 m 3 /yr per m of trench length. Fluid expulsion models indicate that sediment compaction during shallow subduction causes the release of pore water while peak mineral dehydration occurs at temperatures of approximately ∼100°C, 40–30 km landward of the trench. This region is landward of the observed updip extent of seismicity. We posit that in this region the presence of subducting bathymetric relief capped by velocity weakening nannofossil chalk is more important in influencing the updip extent of seismicity than the thermal regime. Key Points: Incoming material compositions at the Costa Rica margin were examined by XRD The sediment and basement contain abundant hydrous smectite and opal Diagenetic reactions significantly affect fluid circulation at this margin